Prevalence of chronic infection foci in patients with dermatoses - A. V. Patrushev; A. V. Samtsov; A. M. Ivanov; A. V. Sukharev; D. D. Asfendiarov (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
This paper presents the results of a retrospective epidemiological study carried out to detect chronic infection foci (CIF) in patients affected by T-cell mediated dermatoses. The values obtained for the CIF prevalence are compared with those in the general population, as well as in the control group. The latter comprised generally healthy people according to the results of in-depth medical examination. It is found that patients with psoriasis demonstrate a higher prevalence of chronic tonsillitis compared to the values both in the general population and in the control group (p = 0.001). Patients with eczema are characterized by an increased prevalence of chronic granulomatous periodontitis, but only in comparison with generally healthy individuals (p = 0.046). The results obtained for patients with atopic dermatitis, lichen planus and alopecia areata are found to be statistically significant for chronic tonsillitis, which occurs therein more frequently than in the general population and in the group of generally healthy people (p = 0.001).